Do Digital Payment Platforms’ Activities affect Corruption? Evidence from Panel of West African Countries - Bibiana Njogo; S. Atanda Mustapha; Chinelo J. Obiekwe (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
The study examines whether the digital payment platforms (ATM, POS, Mobile and Online platforms) affects the level of corruption in selected West African countries. A standard panel data models such as pooled Least Square, random effect and system GMM were adopted to generate the estimators. The findings suggest that the operation of ATM has been deterrent to corruption level in selected West African Countries. This is evidence with the negative effects observed in both the individual and interaction models. The point of sale (POS), Mobile and Online medium of electronic payments have increasing effects on corruption. This is proofed, given the positive signals seen in both the individual and interaction models. The paper further test for robustness through model re-specification and changes in estimation technique and thus, reveals that the coefficients are consistent to model re-specification and advanced estimation procedure. Hence, digital payment platforms significantly influence corruption in West African countries. The implication therefore is that, the regulatory authorities and deposit money banks should advocate for larger usage of the POS and Online digital payment platforms. Also, the use of the mobile platform should be regulated to contend with insecurity it heralds.